Antimicrobial Susceptibility and Characterization of Extended-Spectrum β-Lactamase-Producing Escherichia coli Isolated from Stools of Primary Healthcare Patients in Ethiopia - Deneke Wolde; Tadesse Eguale; Haile Alemayehu; Girmay Medhin; Aklilu Feleke Haile; Mateja Pirs; Katja Strašek Smrdel; Jana Avberšek; Darja Kušar; Tjaša Cerar Kišek; Tea Janko; Andrej Steyer; et al. (MDPI AG, 2024)
Antimicrobial resistance of Escherichia coli is a growing problem in both developed and developing countries. This study aimed to investigate the phenotypic antimicrobial resistance of E. coli isolates (n = 260) isolated from the stool specimen of patients attending public health facilities in Addis Ababa and Hossana. This study also aimed to characterize phenotypically confirmed extended-spectrum beta-lactamase (ESBL)-producing E. coli isolates (n = 22) using whole-genome sequencing. Resistance to 18 different antimicrobials was assessed using the disc diffusion method according to the European Committee on Antimicrobial Susceptibility Testing (EUCAST) guidelines. The highest resistance rate among the E. coli isolates was found for ampicillin (52.7%), followed by trimethoprim-sulfamethoxazole (29.6%). Of all isolates, 50 (19.2%) were multidrug-resistant and 22 (8.5%) were ESBL producers. ESBL genes were detected in 94.7% of the sequenced E. coli isolates, and multiple β-lactamase genes were detected in 57.9% of the isolates. The predominant ESBL gene identified was blaCTX-M-15 (78.9%). The blaTEM-1B gene was detected in combination with other ESBL genes in 57.9% of the isolates, while only one of the sequenced isolates contained the blaTEM-1B gene alone. The blaCTX-M-3 gene was detected in three isolates. The genes blaCTX-M-15 and blaTEM-1B as well as blaCTX-M-15 and blaTEM-169 were confirmed to coexist in 52.6% and 10.5% of the sequenced E. coli isolates, respectively. In addition, blaOXA-1 was identified together with blaCTX-M-15 and blaTEM-1B in one isolate, and in one isolate, blaTEM-169 together with blaCTX-M-15 and blaTEM-1B was found. The results obtained show that measures need to be taken to reduce the spread of drug resistance and ensure the long-term use of available antimicrobials.